Making Sense of Adopted Children's Internal Reality Using Narrative Story Stem Techniques: A Mixed-Methods Synthesis - Tang, Eileen; Bleys, Dries; Vliegen, Nicole (Frontiers in Psychology, 2018)
Background: Extant research on adopted children has consistently shown that early adverse experiences confer vulnerability to myriad developmental problems, which may be mitigated by the “natural intervention” of adoption itself and/or by treatment efforts. Narrative Story Stems Techniques (NSSTs) have been used in research and clinical practice to assess adopted children's developmental profiles in middle childhood. However, no study to date has systematically reviewed this body of literature. Objectives: This paper presents a systematic review of research using NSSTs to make sense of adopted children's internal reality (i.e., perceptions, experiences, and representations), in terms of exploring theoretical perspectives as well as critically synthesizing findings and discussing implications. Methods: State-of-the-art PRISMA guidelines were followed throughout, resulting in the identification of 18 records, comprising six qualitative, 10 quantitative, and two mixed-methods primary papers, reporting on seven unique studies. All records were assessed with regard to methodological quality. Data were extracted and synthesized narratively using an integrated design for mixed-methods synthesis. Results: The findings suggest that, although NSST research with adopted children is still in its infancy, there is relatively robust evidence supporting the use of these techniques to assess and track developmental change in adopted children's attachment representations. In this regard, the non-verbal (aside from the verbal) approach to children's complex internal reality, as well as a more fine-grained (aside from a categorical or dimensional) perspective on children's NSST responses, are highlighted as particularly valuable in tailoring treatment to a particular child's needs and vulnerabilities. Moreover, several promising avenues for future research and clinical application of NSSTs, including the extension to affect-regulatory and mentalizing perspectives, may further our knowledge and understanding of, and thus treatment efforts toward, these often vulnerable children. However, these findings should be interpreted with caution, due to the limited number of studies characterized by considerable methodological heterogeneity. Conclusions: In light of the findings of the present review, we strongly advocate future studies using NSSTs in theoretically and empirically consistent ways, in order to gain a better understanding of adopted children's internal reality in terms of attachment representations, affect-regulatory strategies, and mentalizing processes, and to track changes therein.